LEGAL FRAMEWORK AND INTERVIEWS OF CRIMINAL SUSPECTS FROM THE POINT OF VIEW OF LINGUISTICS (Heritage, 2023)
Linguistics as a scientific discipline is widely applicable in the process of examining all persons who are included in the investigation, which is conducted in order to determine the responsibility of the person for the committed criminal acts, to determine the existence of the very essence of the act.The identification of criminal acts and their perpetrators, the role of individuals in the commission of a criminal act, sometimes relies, in addition to material evidence, on the statements of witnesses, victims and the suspects themselves. When taking statements, police officers use different techniques based on linguistics, from manipulation to identifying the element of non-verbal communication. The paper is based on the author's experience, two years of research and relevant literature.
Keywords: interrogation, suspect, police, criminal offense, linguistics, police, Criminal Procedure Law of the Republic of Srpska